The dynamics of bond market development, stock market development and economic growth: evidence from the G-20 countries - Pradhan, Rudra P. (2020)
Purpose: The paper investigates whether Granger causal relationships exist between bond market development, stock market development, economic growth and two other macroeconomic variables, namely, inflation rate and real interest rate. The study aims to expand the domain of economic growth by including a more in-depth analysis of the possible impact that bond market and stock market development has on economic growth than is normally found in the literature. Design/methodology/approach: This paper uses a panel data set of the G-20 countries for the period 1991-2016. It uses a panel vector auto-regression model to reveal the nature of any Granger causality among the five variables. Findings: The paper provides empirical insights that both bond market development and stock market development are cointegrated with economic growth, inflation rate and real interest rate. The most robust result from the panel Granger causality test is that bond market development, stock market development, inflation rate and real interest rate are demonstrable drivers of economic growth in the long run. Research limitations/implications: Because of the chosen research approach, the research results may lack theoretical foundations. Therefore, perhaps the more fully grounded interactive findings of this study can inspire theorists to fill the missing gap. Practical implications – This paper includes lessons for policymakers in the G-20 countries seeking to stimulate economic growth in the long run and how they need to ensure greater stability of the interest rate and inflation rate as well as fully developing their financial markets, as both bond markets and stock markets are obvious drivers of economic growth. Originality/value: This paper fulfills an identified need to study causal relationships between bond market development, stock market development, economic growth and two other macroeconomic variables, i.e. inflation rate and real interest rate.